The Indian way : learning to communicate with Mother Earth - McLain, Gary (Santa Fe, N.M. : John Muir Publications ; New York, N.Y. : Distributed to the book trade by Norton, 1990)
Describes how Native Americans viewed the environment, lived within it in harmony and respect, and how we today can learn from and practice Indian ways.
"For ages 8 and up"--Cover.
Keywords: Indians of North America -- Social life and customs -- Juvenile literature; Human ecology -- Juvenile literature; Indians of North America -- Social life and customs; Human ecology; Ecology